Modelo de negocio de produccion de leche en la finca el diviso dolores, tolima mediante modelo de pastoreo racional voisin y sistemas de riego en red (2020)
This business model is aimed at generating a family business dedicated to agribusiness. In this way, Inversiones MESGAL S.A.S. It will be a company dedicated to investing in agro-industrial projects in search of generating value through the maximum use of productive lands in the Department of Tolima. In this particular case, it will begin with the EL DIVISO Farm located in the municipality of Dolores, Tolima, which is owned by the shareholders of the company. In this way, the company hopes to implement a milk production project using innovative grazing models based on the work of Professor André Voisin, which seek to generate efficiency in the use of natural resources such as pastures and water sources with the that counts the farm. Thus, what has been done in the El Diviso farm hopes to be an example for the other farms in the region, seeking to promote the implementation of these techniques in search of the improvement and growth of the dairy sector in the south eastern Tolima. In this way, taking into account the growth of the agricultural sector in the country and the support of local and national governments for this industry, the company aims to position the El Diviso farm as a pioneer and leader in milk production, having as objective to supply the demand for milk of the companies dedicated to dairy derivatives in the municipality of Dolores, Tolima. Therefore, the company's strategy focuses on differentiating itself and making the most of the head of cattle per hectare, seeking to obtain the highest profitability, through the proper use of the paddock irrigation system and the fertilization of these. In the same way, following a strategy and organizational characterization, the company hopes to transmit labor and business excellence through the good management of its processes and the effective administration of resources (pastures, water, cattle). Thus, Inversiones MESGAL S.A